Gerakan Nusantara Program on Children’s Nutrition Practices - Gemily, Syilga Cahya; Fikawati, Sandra; Syafiq, Ahmad (Kesmas, 2020)
Gerakan Nusantara is a nutrition education program that aims to change the nutrition knowledge, attitudes, and practices of elementary school children in Indonesia. The program was implemented in 2015–2018 in Jakarta, Bandung, Surabaya, Makassar, Medan, Yogyakarta, Pontianak, East Nusa Tenggara, Pekanbaru, Padang, Jambi, and Sorong. The present study sought to determine the effects of Gerakan Nusantara on the nutrition practices of school-aged children and describe the extent of changes in each nutrition practice component covered by the program. This study used secondary data on Nutrition and Health Knowledge, Attitudes, and Practices studies collected from students participating in the program and involved 6132 school children. The seven nutrition practice components studied were consumption of staple foods, plant protein, animal protein, vegetables, and fruits; milk drinking; and exercise. Significant improvements in fruit consumption and exercise were noted in 2015; all variables improved in 2016; significant changes in the consumption of staple food and plant protein and exercise were recorded in 2017; and significant improvements in the consumption of vegetables, plant protein, and animal protein and milk drinking were noted in 2018. Significant differences in nutrition practices before and after program implementation were noted in each year. Overall, the results demonstrated that Gerakan Nusantara successfully improved the nutrition practices of elementary school children.